Effects of beta-1, 3-glucan supplementation on concentrations of serum metabolites in transition Holstein cows. (October 2020) - Wang, Lin; Xia, Wei-Hao; Wang, Jun-Hong; Fan, Rui-Feng; Niu, Xu-Dong; Wang, Yan-Ming; Li, Qing-Lei; Wang, Zhen-Yong; Wang, Zhong-Hua
Abstract: Objectives of this study were to evaluate the alleviating effects of a commercial beta-1, 3-glucan product (Aleta, containing 50% beta-1, 3-glucan, Kemin Industries) on metabolic stress in transition Holstein cows as reflected by circulating metabolites and enzymes. Fifty-four multiparous Holstein cows were randomly allocated to three groups with 18 cows each. Cows in each group received a commercial basal diet or the basal diet supplemented with Aleta calculated to supply 5 or 10 g of Aleta per cow per day. Blood samples were collected at day −21, 1, and 21 relative to calving for determination of serum triglyceride (TG), total cholesterol (TC), low density lipoprotein cholesterol (LDL-C), high density lipoprotein cholesterol (HDLC), very low density lipoprotein (VLDL), glucose, insulin, β-hydroxybutyric acid (BHBA), aspartate aminotransferase (AST), alanine aminotransferase (ALT), glutamyl transpeptidase (GGT), and non-esterified fatty acid (NEFA). Supplementation with Aleta markedly elevated serum concentrations of TG, TC, HDLC, LDL-C and VLDL, implying its positive effect on lipid metabolism in transition dairy cows. Aleta treatment significantly decreased the serum concentrations of NEFA and BHBA, but markedly elevated the serum concentrations of glucose and insulin. Also, Aleta treatment significantly elevated the dry matter intake and milk production in postpartum cows, indicating the alleviating effect of Aleta on negative energy balance in transition cows. Moreover, Aleta treatment significantly reduced the serum activities of AST, ALT and GGT, indicating its hepatoprotective effect on transition cows. These results suggest that Aleta supplementation may help to improve fat metabolism disorder initiated by negative energy balance in transition dairy cows. Highlights: beta-1, 3-glucan supplementation regulates lipid metabolism in transition cows. beta-1, 3-glucan treatment improves negative energy balance in transition cows. beta-1, 3-glucan exerts hepatoprotective effect for the transition dairy cows.